2015
DOI: 10.1111/jvh.12450
|View full text |Cite
|
Sign up to set email alerts
|

HBx triggers either cellular senescence or cell proliferation depending on cellular phenotype

Abstract: Replicative senescence is a hallmark of chronic liver diseases including chronic hepatitis B virus (HBV) infection, whereas HBV-encoded oncoproteins HBx and preS2 have been found to overcome senescence. HBx possesses a C-terminal truncation mainly in hepatocellular carcinomas but also in noncancerous liver tissues. Here, by cell counting, BrdU incorporation, MTT proliferation assay, cell cycle analysis, SA-βgal staining and Western blotting in primary and malignant cells, we investigated the effect of HBx C-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…This particular protein has been shown to inhibit p53 activity, binding to the C terminus of p53, thereby blocking apoptosis 30 . Accordingly, HBx protein exerts a pro‐senescent role, based upon increased p16 (INK4a) and p21 (Waf1/Cip1) expression and a decreased Rb phosphorylation status 31 . Extracted results confirmed that HBx C‐terminal mutants can trigger cellular senescence in primary MRC5 cells, malignant liver cells Huh7 and SK‐Hep1.…”
Section: Interplay Between Hbv and Cellular Senescencementioning
confidence: 77%
See 1 more Smart Citation
“…This particular protein has been shown to inhibit p53 activity, binding to the C terminus of p53, thereby blocking apoptosis 30 . Accordingly, HBx protein exerts a pro‐senescent role, based upon increased p16 (INK4a) and p21 (Waf1/Cip1) expression and a decreased Rb phosphorylation status 31 . Extracted results confirmed that HBx C‐terminal mutants can trigger cellular senescence in primary MRC5 cells, malignant liver cells Huh7 and SK‐Hep1.…”
Section: Interplay Between Hbv and Cellular Senescencementioning
confidence: 77%
“…Extracted results confirmed that HBx C‐terminal mutants can trigger cellular senescence in primary MRC5 cells, malignant liver cells Huh7 and SK‐Hep1. In contrast, these mutants promoted the proliferation of HepG2 malignant liver cells 31 . Excessive secretion of SASP components has also been reported in chronic hepatitis B, while HBV infection has been associated with elevated levels of angiogenin‐2.…”
Section: Interplay Between Hbv and Cellular Senescencementioning
confidence: 95%
“…3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide (MTT; Sigma‐Aldrich) assay was performed as previously described . Cells in 96‐well plate were transfected and allowed to grow for 4 days and then treated with 1 mg mL −1 MTT solution for 4 hours at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT; Sigma-Aldrich) assay was performed as previously described. [27][28][29]…”
Section: Cell Proliferation (Mtt) Assaymentioning
confidence: 99%
“…Several studies have demonstrated that HCC-associated HBx mutants more strongly promote oncogenesis than intact HBx 11 . For example, HBx mutants with a C-terminal truncation promote or inhibit cell proliferation in a manner that depends on deletion sites 12 . However, the molecular mechanisms by which the functions of HBx are altered in the presence of HBx mutations and cause the promotion of HBV-related hepatocarcinogenesis have not yet been elucidated in detail.…”
Section: Introductionmentioning
confidence: 99%